Effect of Flurbiprofen spray on postoperative tonsillectomy pain - Abdulkhaliq Kerim Hamad Emin (Advanced Medical Journal)
Background and objectives: Tonsillectomy is one of the most frequently performed surgical procedures. Up to date there are no guidelines for pain control following tonsillectomy. The aim was to determine whether oral spray flurbipro- fen reduces pain and has an influence on wound healing following tonsillectomy.